Water binding stabilizes stacked conformations of ferrocene containing sheet-like aromatic oligoamides. Issue 25 (27th April 2021) - Liu, Ya-Zhou; Mu, Xiao; Chan, Cheih-Kai; Robeyns, Koen; Wang, Cheng-Chung; Singleton, Michael L.
Abstract : The encapsulation of discrete water molecules in flexible sheet-like aromatic oligoamide foldamers, as evidenced by structural and spectroscopic studies, stabilizes their structure. Abstract : While water clusters play an essential role in the stability of biological structures, their ability to stabilize synthetic oligomers is less understood. We have synthesized a heptameric sheet-like aromatic oligoamide foldamer with ferrocene as turn unit. It shows strong interactions with water in the solid state and in solution. The water binding limits the fluxional processes resulting from the flexible ferrocene unit, highlighting the importance of such interactions for conformational studies on this class of molecule.